The View of Slang Words in the Movie “No Hard Feelings” (2023) - Hafsha Fauzia Ramadhan; Ervina CM Simatupang (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This paper explores the types of slang words in the movie "No Hard Feelings," (2023) and analyses the significance within the context of the movie and contemporary Sociolinguistics. By analyzing the dialogue, the research highlights how slang words enhance character development, drives narrative progression, and reflects cultural authenticity. The research delves into the sociolinguistic implications of movie slang, examining its role in mirroring and shaping real-world language trends. The findings suggest that the strategic use of slang in the movie not only enriches the film’s realism but also influences audience perceptions and everyday communication patterns. This study contributes to a deeper understanding of the dynamic relationship between film dialogue and sociolinguistic evolution, emphasizing the cultural resonance of cinematic language choices. In conclusion, the strategic use of different types of slang in "No Hard Feelings" demonstrates the power of language to convey character, context, and culture. It underscores the film's commitment to capturing the nuances of modern life, making the characters' interactions both believable and compelling